Policies in support of lending following the coronavirus (COVID-19) pandemic - Katarzyna Budnik; Ivan Dimitrov; Johannes Groß; Martina Jancoková; Max Lampe; Bianca Sorvillo; Anze Stular; Matjaz Volk (European Central Bank (ECB), 2021)
This paper looks at the impact of mitigation policies implemented by supervisory and macroprudential authorities as well as national governments in the euro area during the coronavirus (COVID-19) pandemic to support lending to the real economy. The impact assessment concerns joint, and individual, effect of supervisory measures introduced by the ECB Banking Supervision, a reduction in macroprudential buffers put forward by national macroprudential authorities, and public moratoria and guarantee schemes. The analysis has been conducted in the first half of 2020, in a situation of high uncertainty about how the crisis will develop in the future. Against this backdrop, it proposes a method of addressing such uncertainty by assessing the impact of policies across a full range of scenarios. We find that the supervisory, macroprudential and government policies should have helped to maintain higher lending to the non-financial private sector (around 5% higher than lending in the absence of policy measures) and, in particular, to non-financial corporations (12% higher than lending in the absence of policy measures), preventing further amplification of the recession via the banking sector. The national and supervisory and macroprudential actions have reinforced each other, and have been jointly able to affect a broader share of the banking sector.
Keywords: E37; E58; G21; G28; 330; COVID-19; impact assessment; banking sector; real-financial feedbackmechanism